Strengthening character education through Al-Islam and Kemuhammadiyahan based on merdeka curriculu - Firdaus, Firdaus; Makhful, Makhful (ATTARBIYAH: Journal of Islamic Culture and Education, 2023)
The aim of this research is to explore approaches to strengthening character education, describe Al-Islam and Muhammadiyahan learning models, and analyze supporting and inhibiting factors for strengthening character education through Al-Islam and Muhammadiyahan based on the Independent Curriculum. This research is field research with a qualitative approach at SMK Muhammadiyah Sampang. The technique for taking subjects in this research used purposive sampling, data was obtained by interviews, observation and documentation. The results of this research explain that strengthening character education is carried out through several activities such as the habit of tadarus, midday prayers in congregation, midday prayers, Friday routine studies, and Sunday morning studies. These activities are integrated with ISMUBA subjects which include aqidah, morals, worship, al-Qur'an, dates, muhammadiyahan and Arabic. The ISMUBA learning model uses the Problem Based Learning (PBL) model by presenting factual cases related to the material to be studied. Supporting factors for strengthening character education are the professionalism of human resources (teachers and staff), massive training and workshops in the Independent Curriculum. Meanwhile, the inhibiting factors are the absence of guidebooks for students and teachers, low student interest and awareness of ISMUBA material, and family background.